Zina Dalam Perspektif Hukum Pidana Islam - Rzky Amelia; Soleha, Maulida; Septian Yoga Pangestu, Muhammad; Lahmudinur (PT. Pustaka Andil Lestari, 2025)
This study examines zina from the perspective of Islamic criminal law, focusing on its definition, legal requirements, sanctions, and the underlying wisdom behind its prohibition. The research stems from the increasing prevalence of free association among youth, which contributes to moral decline and social problems. Employing library research with a normative–theological approach, data were collected from the Qur’an, Hadith, classical and contemporary fiqh, as well as Indonesian positive law. The findings show that zina is defined as unlawful sexual intercourse outside a valid marriage contract and is categorized as a jarimah hudud with strict evidentiary requirements, such as the testimony of four male witnesses or voluntary confession. The sanctions vary according to the perpetrator’s marital status: one hundred lashes and exile for unmarried offenders, and stoning to death for married offenders. In comparison, Indonesian law treats zina as a complaint-based offense with lighter penalties, whereas Islamic law emphasizes moral protection and deterrence. The prohibition of zina serves to protect honor, lineage, health, family harmony, and overall morality. This research highlights the importance of strengthening moral education and integrating the values of Islamic criminal law into national legislation to address contemporary social challenges.